2017
DOI: 10.2139/ssrn.2912259
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Booms, Domestic Busts: The Global Dimension of Banking Crises

Abstract: This paper provides novel empirical evidence showing that foreign financial developments are a powerful predictor of domestic banking crises. Using a new data set for 38 advanced and emerging economies over 1970-2011, we show that credit growth in the rest of the world has a large positive effect on the probability of banking crises taking place at home, even when controlling for domestic credit growth. Our results suggest that this effect is larger for financially open economies, and is consistent with transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…These findings have some parallels with the early-warning literature, where faster global credit growth is found to be a significant predictor of crises (Cesa-Bianchi et al, 2019;Bluwstein et al, 2020). However, our results are more general, suggesting that this predictability arises specifically from the association between foreign variables and the left tail of the domestic GDP growth distribution.…”
Section: Coefficients Across Quantilessupporting
confidence: 87%
See 1 more Smart Citation
“…These findings have some parallels with the early-warning literature, where faster global credit growth is found to be a significant predictor of crises (Cesa-Bianchi et al, 2019;Bluwstein et al, 2020). However, our results are more general, suggesting that this predictability arises specifically from the association between foreign variables and the left tail of the domestic GDP growth distribution.…”
Section: Coefficients Across Quantilessupporting
confidence: 87%
“…We include the foreign-weighted counterparts of each of the indicators in the foreign variable set X * i,t . 6 This variable choice is, in part, motivated by evidence that global financial market indicators and credit quantities tend to predict domestic financial crises (Cesa-Bianchi et al, 2019;Bluwstein et al, 2020). For our baseline results, we construct foreignweighted variables using data on bilateral trade linkages.…”
Section: Foreign Covariatesmentioning
confidence: 99%
“…During the global financial crisis, and only then, by far the most important predictor is global credit. This may be partly driven by financial globalisation which has magnified the importance of international credit growth (Cesa-Bianchi et al, 2019). For example, Germany and Switzerland experienced negative domestic credit to GDP growth before the global financial crisis.…”
Section: The Importance Of Variables Across Timementioning
confidence: 99%
“…Kaminsky and Reinhart (1999); Bussiere and Fratzscher (2006) ;Drehmann et al (2011); Frankel and Saravelos (2012); Schularick and Taylor (2012); Drehmann and Juselius (2014); Babeckỳ et al (2014); Giese et al (2014)). This literature typically identified domestic private credit or credit-to-GDP growth and indebtedness as key predictors of financial crises, with more recent work (Alessi and Detken, 2011;Duca and Peltonen, 2013;Cesa-Bianchi et al, 2019) also highlighting the importance of global credit growth in predicting crisis after 1970. Our results are in line with these findings.…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical support for this international banking channel and the associated global credit cycle. Cesa- Bianchi et al (2017) have found evidence of a common factor explaining up to half of the variance of domestic credit growth in 38 advanced and emerging countries in recent years and support for the transmission channels being mostly through the financial sector rather than trade and real effects. Baskaya et al (2017aBaskaya et al ( , 2017b have also found supporting evidence in the case of Turkey.…”
Section: The Global Banking Channelmentioning
confidence: 99%